2007
DOI: 10.1111/j.1600-0668.2007.00475.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analyses of the associations of respiratory health effects with dampness and mold in homes

Abstract: IntroductionThe association of adverse health effects with dampness and mold in buildings has been the subject of much research. Most studies on this topic have found an increased risk of one or more adverse health effects in buildings with signs of dampness or visible mold. The Institute of Medicine (IOM) of the National Academy of Sciences recently completed a critical review (IOM, 2004) of this scientific literature. The IOM concluded that excessive indoor dampness is a public health problem, noted that dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
351
3
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 578 publications
(403 citation statements)
references
References 40 publications
19
351
3
10
Order By: Relevance
“…On the other hand, a recently published longitudinal study from Sweden found that self reported dampness or mold could be biased, since the baseline findings of a strong association between dampness and allergies disappeared in the follow-up study 5 years later [40]. This could be due to a reporting bias in a country (Sweden) where the lay public has been educated on the association of dampness/mold with asthma [34,40,41]. We do not know whether the current positive associations were due to a reporting bias; possibly, home environment questionnaires could be validated by blinded objective observations in Chinese local homes, or by longitudinal studies, but this issue requires further studies.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a recently published longitudinal study from Sweden found that self reported dampness or mold could be biased, since the baseline findings of a strong association between dampness and allergies disappeared in the follow-up study 5 years later [40]. This could be due to a reporting bias in a country (Sweden) where the lay public has been educated on the association of dampness/mold with asthma [34,40,41]. We do not know whether the current positive associations were due to a reporting bias; possibly, home environment questionnaires could be validated by blinded objective observations in Chinese local homes, or by longitudinal studies, but this issue requires further studies.…”
Section: Resultsmentioning
confidence: 99%
“…Ethical approval for this cross sectional study was granted by the University of Exeter worldwide public health concern because of its association with an increased risk of 76 allergic diseases (Fisk et al, 2007;, now elevated concentrations of spores and hyphal fragments (Sharpe et al, 2014c), 80 which in turn is influenced by the type of material (Andersen et al, 2011), moisture 81 (Flannigan et al, 2011), indoor air velocity, and the types of fungi present (Mensah-…”
mentioning
confidence: 99%
“…Excessive humidity, leading to mould and house dust mite proliferation, was ranked first by far. A recent meta-analysis demonstrated that living in a humid environment is related to a significant risk of developing de novo asthma and decreasing asthma control in asthmatic patients [24]. Such conclusions have also been reached in a large European collaborative epidemiological survey [25].…”
Section: Current Achievementsmentioning
confidence: 75%